19F Barcoding Enables Multiplex Detection of Biomarkers Associated with Organ Injury and Cancer. (14th October 2022) - Luo, Xiangjie; Kang, Bilun; Chi, Xiaoqin; Xiong, Hui; Chen, Dongxia; Fan, Yifan; Li, Lingxuan; Chen, Limin; Li, Ao; Gao, Jinhao; Lin, Hongyu
Abstract: Simultaneous detection of multiple biomarkers in complex environments is critical for the in‐depth exploration of different biological processes, which is challenging for many current analytical methods due to various limitations. Herein, we report a strategy of 19 F barcoding which takes the advantages of 19 F's high magnetic resonance (MR) sensitivity, prompt signal response to environmental changes, negligible biological background, quantitative signal output, and multiplex capacity. A set of 19 F‐barcoded sensors responding to different biomarkers involved in organ injury and cancer are designed, synthesized, and characterized. With these sensors, we accomplish concurrent assessment of different biomarkers in the samples collected from the mice with drug‐induced liver/kidney injury or tumor, illustrating the feasibility of this approach for multiplexed detection of different biomarkers in complex environments during various biological processes. Abstract : A set of molecular sensors with 19 F barcodes enables multiplex detection of different biomarkers associated with organ injury and cancer. The barcoding strategy takes the advantage of 19 F's high magnetic resonance (MR) sensitivity, prompt signal response to environmental changes, negligible biological background, quantitative signal output and multiplex capacity.